Dialogue transatlantique du travail: le potentiel du developpement (Халықаралық қатынастар және халықаралық құқық сериясы, 2016)
The subject of social relationship of EU and the USA is sufficiently extensive. The author's attention was concentrated on the social dialogue which part is cooperation between the government, trade unions and workers on both sides of the Atlantic. In this article the author analyzes the development trends of the Transatlantic Labor Dialogue which was created after the Cold War for the joint solution of labor problems. The historical retrospective indicates the existence of similar labor problems in Europe and the USA. The financial crisis has forced the governments of EU and the USA to raise again the issue of effective cooperation in labor questions. This is indicated bythe existing sources.By combining theirefforts and working actively in this area, EU and the USA will be able to achieve considerable results in theworld of work.